STUDI PENENTUAN LOKASI RAWAN KECELAKAAN PADA RUAS JALAN NASIONAL TIPE 2/2 UD DI KOTA BANDA ACEH - Rahmat Sofyan; Meylis Safriani (Universitas Teuku Umar, 2017)
The number of accidents that occurred in the city of Banda Aceh between the years 2012 - 2014 which recorded as many as 425 accidents. The number of accidents needs to be reduced given the importance of road users' safety. Some of the existing national roads in Banda Aceh City have the potential for accidents. The national road in Banda Aceh City has 3 types, type 6/2 D, type 4/2 D, and type 2/2 UD. Study on the determination of accident prone locations to minimize the number of accidents that occur should be done especially in the city of Banda Aceh which is the capital of Aceh province. In this study, a study was conducted on the location of accident-prone on the national road in Banda Aceh City with type 2/2 UD. The roads included in this type are Jalan Laksamana Malahayati, Jalan Prof. Dr. Ibrahim Hasan, and Jalan Simpang Rima-Bts Banda. This study aims to analyze the determination of accident prone locations based on accident data on national roads type 2/2 UD in Banda Aceh City and analyze safety issues in accident-prone locations based on accident data, traffic conflicts, and direct observation on location Accident prone. The ranking of vulnerable locations is done using 4 criteria, namely: 1) accident frequency, 2) Equivalent property damage only (EPDO), 3) accident rate, and 4) critical rate. The ranking comparison of these 4 criteria will be used as a reference to determine the location of the most prone to accident. From the analysis result, it was found that the accident-prone location of the three roads on the 2/2 UD road segment is Jalan Laksamana Malahayati and the road segment or the most accident-prone location is Jalan Laksamana Malahayati (Km 3 - 4). This is based on the assessment of the location that has the highest accident rate value and exceeds the critical crash rate on each of those road segments. Keywords: traffic accident, road segment, accident prone location